DIFFICULTIES IN LISTENING COMPREHENSION FACED BY THIRD SEMESTER IN THE EXTENSIVE LISTENING COURSE - Haidah Situmorang; Febrika Dwi Lestari; Christina Natalina Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the difficulties in listening comprehension faced by third-semester students in the Extensive Listening course at the English Department of HKBP Nommensen University Medan. The research employed a qualitative approach with a descriptive design to explore the types of listening difficulties experienced by students and the factors contributing to those difficulties. The participants consisted of third-semester students enrolled in the Extensive Listening course during the 2025/2026 academic year. Data were collected through classroom observation, questionnaires, and semi-structured interviews. The questionnaire involved 30 students, while in-depth interviews were conducted with 10 selected participants using purposive sampling.The findings reveal that students experience various listening difficulties, including limited vocabulary, unfamiliar grammatical structures, pronunciation differences, unfamiliar accents, fast speech rate, and reduced forms in connected speech. Among these factors, fast speech rate and unfamiliar vocabulary were identified as the most dominant difficulties affecting students’ listening comprehension. Observation and interview results further indicate that long listening passages and technical issues related to audio quality also contribute to students’ comprehension problems. Overall, the study concludes that students’ listening difficulties are influenced by both linguistic and technical factors, with linguistic factors playing a more significant role. These findings suggest the need for improved listening materials, varied exposure to accents, and appropriate speech rates to enhance students’ listening comprehension skills.